Vibration Damage Analysis of Bottom Hole Assembly Under Axial Impact Based on Dynamic Analysis - Qilong Xue; Yafeng Li; Jianbo Jia; Lun Zhao (Applied Sciences)
Impact Drilling Technology is one of the most effective methods for enhancing the penetration rate and efficiency in hard rock formations. Downhole axial vibration impact tools can provide a stable impact load, but they also increase the complexity of the Bottom Hole Assembly (BHA) motion. Addressing the problem of vibration fatigue in the lower BHA when subjected to high-frequency impact stresses during impact drilling, this study utilizes finite-element impact modules and Design-Life fatigue analysis software to establish a nonlinear dynamic model of the drill string assembly under axial excitation. It investigates the influence patterns of control parameters, such as the impact energy and impact frequency, on BHA vibration damage and rock-breaking efficiency. The results show that the vibration characteristics of the BHA are significantly affected by the impact tool’s control parameters. Increasing the input impact energy intensifies the amplitude of alternating stress in the drill string system. Meanwhile, the equivalent stress fluctuation of the drill string tends to stabilize at high frequencies above 100 Hz, indicating that high-frequency impacts are beneficial for mitigating vibration damage and prolonging the service life of the BHA. This study provides a theoretical basis for reducing the drill string fatigue damage and optimizing the drilling parameters for an improved performance.